(1)因为a1=f(1)-c=-c,
a2=[f(2)-c]-[f(1)-c]=-,
a3=[f(3)-c]-[f(2)-c]=-.
又数列{an}成等比数列,
所以a1===-=-c,
解得c=1.…(2分)
又公比q==,
所以an=-•()n-1=-2•()n-1,n∈N*.…(3分)
(2)∵Sn-Sn-1=+,n≥2,
即(-)(+)=+,n≥2
∴-=1,(n≥2)…(5分)
又===1
∴数列{}构成一个首项为1,公差为1的等差数列,
∴=1+(n-1)×1=n,∴Sn=n2.…(6分)
(3)由(2)得Sn=n2,
当n≥2时,bn=Sn-Sn-1=n2-(n-1)2=2n-1,(*)
又b1=S1=1,适合(*)式
∴bn=2n-1,(n∈N*)…(8分)
∵==(-),
∴Tn=+++…+
=(1-)+(-)+(-)+…+(-)
=(1-)=,…(10分)
由Tn=>,得n>,
故满足Tn>的最小正整数为112.…(11分)
(4)cn==(1-2n)•3n.…(12分)
∴Pn=(-1)×3+(-3)×32+(-5)×33+…+(1-2n)×3n①3Pn=(-1)×32+(-3)×33+(-5)×34+…+(3-2n)×3n+(1-2n)×3n+1②
②-①得2Pn=3+2×32+2×33+…+2×3n+(1-2n)×3n+1
| =3+2×+(1-2n)×3n+1 | =(2-2n)•3n+1-6. |
| |
∴Pn=(1-n)•3n+1-3.…(14分)